REVIEW AFRICAN SWINE FEVER: PENULARAN, FAKTOR RESIKO DAN DAMPAK EKONOMI YANG DITIMBULKAN - Petrus Malo Bulu (Politeknik Pertanian Negeri Kupang, 2022)
African swine fever or also known as African Swine Fever (ASF) is a serious viral disease in domestic pigs and wild boars and is highly contagious which causes disease in pigs, generally characterized by high fever, hemorrhages, ataxia, and severe depression. African swine fever virus is a major threat to pig production as it has mortality rates approaching 100%. By early 2018, ASF had spread throughout China, Mongolia, Korea, Vietnam, Laos, Cambodia, Myanmar, Philippines, Hong Kong, Indonesia, Timor-Leste and Papua New Guinea. The disease is spread through direct contact with infected animals or their body fluids or indirectly through contaminated vehicles, equipment or food containing meat from infected pigs. Several risk factors have contributed to the introduction and transmission of the disease into farmers/countries including biosecurity practices, animal movements, and husbandry practices. The disease has caused huge direct and indirect economic losses around the world. It currently has no specific treatment or vaccine available.Key Words: African Swine Fever, Demam Babi Afrika, Babi, NTT